Seasonal variation in total water storage in California inferred from GPS observations of vertical land motion. Issue 6 (31st March 2014) - Argus, Donald F.; Fu, Yuning; Landerer, Felix W.
Abstract GPS is accurately recording vertical motion of Earth's surface in elastic response to seasonal changes in surface water storage in California. California's mountains subside up to 12 mm in the fall and winter due to the load of snow and rain and then rise an identical amount in the spring and summer when the snow melts, the rain runs off, and soil moisture evaporates. We invert the GPS observations of seasonal vertical motions to infer changes in equivalent water thickness. GPS resolves the distribution of change in total water across California's physiographic provinces at a resolution of 50 km, compared to 200 km resolution from the Gravity Recovery and Climate Experiment. The seasonal surface water thickness change is 0.6 m in the Sierra Nevada, Klamath, and southern Cascade Mountains and decreases sharply to about 0.1 m east into the Great Basin and west toward the Pacific coast. GPS provides an independent inference of change in total surface water, indicating water storage to be on average 50% larger than in the NLDAS‐Noah hydrology model, likely due to larger changes in snow and reservoir water than in the model. Seismicity and land uplift produced by groundwater loss in California's Central Valley is also being evaluated [Amos et al., 2014].